Motherhood in prison: reconciling the irreconcilable - Freitas, Ana Maísa (2016)
Few studies have allowed imprisoned mothers to speak directly about motherhood. In this work, 20 convicted Portuguese mothers were interviewed about their experience of motherhood: Ten were raising their children in prison, and 10 were performing their roles as mothers from prison. The study aimed to understand the potential benefits and detriments of motherhood in both circumstances, and to identify what measures could improve the mothers’ conditions. Using thematic analysis, the findings indicate that women whose children live with them in prison experience some advantages, but motherhood also increases suffering due to restrictions on liberty.